2022
DOI: 10.1186/s12906-022-03515-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of curcumin supplementation on vitamin D levels in women with premenstrual syndrome and dysmenorrhea: a randomized controlled study

Abstract: Background Vitamin D has an established role in female reproduction. There is also evidence for an association between vitamin D levels and menstrual problems such as premenstrual syndrome (PMS) and dysmenorrhea. Curcumin, is a bioactive polyphenol constituent of turmeric, that can potentially interact with vitamin D receptors and its molecular targets. This study evaluated the effects of curcumin on vitamin D levels in young women with PMS and dysmenorrhea. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 60 publications
(57 reference statements)
0
29
1
2
Order By: Relevance
“…According to another study, Cur can also decrease the IL-1α induced expression of RANKL in BMSCs, leading to the suppression of osteclastogenesis and inducing apoptosis of osteoclasts (Ozaki et al, 2000;Bharti et al, 2004;Gu et al, 2012;Sahebkar et al, 2016). Moreover, some studies have confirmed the relationship between curcumin and Vit D. The effectiveness of curcumin in improving Vit D deficiency, especially in women with PMS and dysmenorrhea (Arabnezhad et al, 2022). Therefore, in this study, we have utilized the electrospinning method to fabricate a nanofibrous scaffold doped with Vit D and Cur, as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 94%
“…According to another study, Cur can also decrease the IL-1α induced expression of RANKL in BMSCs, leading to the suppression of osteclastogenesis and inducing apoptosis of osteoclasts (Ozaki et al, 2000;Bharti et al, 2004;Gu et al, 2012;Sahebkar et al, 2016). Moreover, some studies have confirmed the relationship between curcumin and Vit D. The effectiveness of curcumin in improving Vit D deficiency, especially in women with PMS and dysmenorrhea (Arabnezhad et al, 2022). Therefore, in this study, we have utilized the electrospinning method to fabricate a nanofibrous scaffold doped with Vit D and Cur, as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 94%
“…Arabnezhad et al [ 51 ] reported that curcumin improves serum vitamin D levels. Xin et al [ 104 ] described that curcumin induces overexpression of vitamin D receptor (VDR) in osteoblasts and femurs probably involved in the protective effect of curcumin on bone loss created by microgravity although curcumin administration has no considerable effect on serum 1,25-(OH)2D3 concentration.…”
Section: Literature Review Based On Research Questionsmentioning
confidence: 99%
“…We excluded the following RCTs from the meta-analysis as reasoned: Arabnezhad et al (2022) [1] included a PSST study only before the intervention. Maskani et al (2020) [31] and Ozgoli (2011) [32] were written in Persian Language, and the data for symptoms were presented as percentages and number.…”
Section: Literature Review Of the Randomized Controlled Trials Based ...mentioning
confidence: 99%
“…Premenstrual somatic and psycho-behavioural symptoms are categorized by a cyclic pattern that is obvious within the luteal phase [1], and they significantly affect quality of life with more frequent visits to hospitals parenting problems, decreased work productivity, and impaired individual and societal relationships [2][3][4]. It is a common and recurrent gynaecological problem [1], and 20-30% of reproductive-age women experience clinically significant premenstrual syndrome (PMS) symptoms [5]. The main psychological range of PMS symptoms includes anxiety and depression [3,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation